Comorbidity Is a Competing Factor for Disease Recurrence Postnephrectomy. Issue 5 (May 2017) - Reinstatler, Lael; Klaassen, Zachary; Madi, Rabii; Terris, Martha K.; Moses, Kelvin A.
Abstract : Objective: There is a relation between tumor stage and grade with the risk of cancer recurrence in patients undergoing surgical treatment for kidney cancer. The association of patient comorbidity with disease recurrence is less well characterized. The objective of this study was to explore the association between comorbidity and the recurrence of kidney cancer. Methods: We performed a retrospective analysis of 263 patients who received a partial or radical nephrectomy from January 1, 2000 through April 30, 2013. Patient data included race, sex, body mass index, age-adjusted Charlson Comorbidity Index (aaCCI) score, tumor histology, tumor T classification, and Fuhrman grade. The primary outcome was cancer recurrence, either local or distant. Logistic regression was used to assess the association of these risk factors with the outcome. Results: The median follow-up time was 19.6 months (interquartile range 5.2–53.7). There were 101 (38.4%) African American patients and 150 (57.0%) men. The median body mass index was 28.3 and the median aaCCI was 3.0. The Fuhrman grade was G1 in 9.5% of patients, G2 in 45.2%, G3 in 32.8%, and G4 in 12.5%. Nineteen (7.2%) patients experienced disease recurrence, including 13 (4.9%) patients with metastatic disease. The risk factors significantly associated with recurrence included Fuhrman grade (odds ratio [OR] 3.0, 95% confidence interval [CI] 1.23–7.30), tumor T classification (OR 1.33, 95% CI 1.00–1.76), and CCI (OR 0.74, 95% CI 0.57–0.95). Conclusions: Physiologic factors, in addition to tumor characteristics, play a significant role in predicting cancer-specific survival in patients with kidney cancer. The reduced odds of recurrence with higher aaCCI may indicate that competing health factors have an impact before recurrence on survival in certain patients. Abstract : The association of patient comorbidity with renal cell carcinoma recurrence postnephrectomy is not well characterized. A retrospective review of 263 patients undergoing partial or radical nephrectomy for a renal mass demonstrated that 19 (7.2%) patients experienced disease recurrence, including 13 (4.9%) patients with metastatic disease. The risk factors significantly associated with recurrence included Fuhrman grade, tumor T classification, and age-adjusted Charlson Comorbidity Index score.